Brain Gym for Physical Motor Development in Children Aged 3-4 Years - Kundarwati, Asih Tri; Khasanah, Nur Putri; Fauziyah, Nur (Proceedings International Conference on Education Innovation and Social Science, 2023)
Early Childhood Education is a place or tools of learning for children before entering formal education. Early Childhood Education uses the concept of learning throught playing. By playing, it is hoped that children will feel a positive impact and grow well. Brain Gym or Brain Gymnastics is a method to improve concentration abilities in early childhood with simple movements. Where early childhood requires stimulation from outside to support the growth and development of physical motor, social emotional and language. The benefits of brain gym are (1). to stimulate the level of concentration and focus in children. (2). Maintaining body fitness. (3). Overcoming children’s learning problems. (4). Stimulates physical motor development. (5). Balancing the right brain and left brain. The purpose of the study using the brain gym is to find out abaou this brain exercise activity to improve physical motor development and concentration levels in children, the children’s body is healthy and strong and can improve the quality the exist in children. The method used in this research is literature study. Children easily socialize with playmates and communicate actively with educators and friends. Brain gym affects children’s concentration and interest inlearning to increase. This is interrelated between the brain and the physical child.